The problem of preparing future educators of preschool educational institutions for patriotic upbringing of older preschool children - Volodymyrivna Filimonova, Tetiana (2021)
The problem of teacher training of civic children education of older preschool age is disclosed. The condition of investigated problem is analyzed, the essence of the key research concepts is clarified, the criteria, indicators and levels of civic children education of older preschool age are disclosed. The purpose of the study is to determine certain levels of preparedness of future preschool teachers for patriotic education of older preschool age, to highlight the structural-functional model of the effective formation of future teachers of preschool educational institutions for civic education of older preschool age, justification and testing of pedagogical conditions for its implementation. Studying the reality of readiness of future teachers for the patriotic education of older preschool age allowed identifying the following levels of readiness of future teachers in the control and experimental groups: high, sufficient, average, low. In the course of study, we developed a structural-functional model for the formation of the readiness of future tutor for the civic education of older preschool age with the following structural components: purpose, principles, methods, forms, means, structural components, pedagogical conditions, criteria, indicators, levels and results – the readiness of future teacher for the patriotic education of senior preschool age. The following principles are related to the pedagogical principles underlying the model: the principle of humanization, personalization, individualization, professional competence, optimization.